GAUCHERIE MANUELLE ET PERFORMANCES SCOLAIRES - Badolo, Léopold (European Scientific Journal, ESJ, 2012)
This article interests in the bond between left manual laterality and the school performances. It poses’assumption that manual sinistrality obstructs the school apprenticeships and maintains, so a negative bond with the performances. To test it, 67 pupils of level CM2 (including 44 boys and 23 girls) were surveyed. The analysis of results does not provide the elements to confirm the formulated assumption. The left-handeds persons are located at various performance levels (weak, average, strong). The quality of performances is not the’ prerogative of a type given individual (left or right handed).